A detector to measure 9Li production rate in liquid scintillator at the earth’s surface by cosmic ray muons - Smith, Mark A. (Kansas State University, 2009)
The next generation of nuclear fission reactor based neutrino experiments seeking to measure the Theta-13 mixing angle rely upon measurements made by detectors placed close to the reactor, and therefore less shielded from cosmic ray muons by the earth. 9Li production in liquid scintillator by these cosmic ray muons becomes a serious problem for these experiments that must be dealt with since the 9Li production rate is still a significant fraction of the neutrino interaction rate. This 9Li background reduces the experiment’s sensitivity to measure the Theta-13 mixing angle. This thesis discusses a small detector designed to measure the 9Li production rate in liquid scintillator at the earth’s surface by cosmic ray muons. The detector was designed, built, and finally, calibrated. The ability to find the signals necessary to actually measure the 9Li production rate is shown, establishing that this detector will be able to measure the production rate. A 90% significance level upper limit for the 9Li-like production rate, based on only 3.5 days worth of data, is reported as 213 9Li-like events per day per ton.
Keywords: Lithium 9; Neutrino background; Neutrino detector; Physics, Elementary Particles and High Energy (0798)